CONTINUOUS SWIMMING TRAINING IN MODERATE INTENSITY DECREASED FOLLICLE STIMULATING HORMONE LEVEL IN FEMALE MICE ON A HIGH-CALORIE DIET - Amalia Ramadhani; Sri Ratna Dwiningsih; Lilik Herawati (UNIVERSITAS AIRLANGGA, 2023)
Background: The increase of calorie intake can increase the risk of obesity and diabetes mellitus. One of the efforts to reduce the risk is doing physical exercise. Types of physical exercise that can affect the system of female reproduction are not clearly defined. Purpose: To analyse the effect of moderate intensity continuous physical exercise on FSH levels in female rats exposed to a high-calorie diet. Methods: Laboratory experimental was research with Randomized Post test only Control Group Design. Sampel size was 27 rats (150-200, adults) in the estrus phase, then divided into 3 groups (negative control group, positive control group (high-calorie diet), and the Moderate Intensity Continuous Training group (MICT with high-calorie diet)). Results: The results showed that there was an significant effect of continuous physical exercise in moderate intensity on FSH level in female rats exposed to other group. The FSH level in the MICT group had the lowes level (16.78 ±4.83 mIU/ml). Conclusion: There is an effect of MICT on FSH level decreases in female rats exposed to a high diet calories. This can be caused, that high-calorie diet can inhibit GnRH secretion and continuous moderate-intensity physical exercise changes the rat energy metabolism